2002
DOI: 10.1207/s15374424jccp3104_10
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence of Reliability and Validity of the Child Symptom Inventory-4: Parent Checklist in Clinically Referred Boys

Abstract: Examined reliability and validity of the parent version of the Child Symptom Inventory (CSI-4) in 247 boys between 6.0 and 10 years 11 months old referred for evaluation of behavioral and emotional problems. The CSI-4 is a behavior rating scale whose items correspond to the symptoms of disorders defined by the Diagnostic and Statistical Manual of Mental Disorders (4th ed. [DSM-IV]; American Psychiatric Association, 1994). Results indicated satisfactory internal consistency reliability, test-retest reliability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(103 citation statements)
references
References 27 publications
7
96
0
Order By: Relevance
“…In addition, the study provides initial evidence for the factorial validity of teacher ratings of DSM-IV-TR-defined symptoms of ODD and CD in clinical populations. Since similar findings were reported for parent-completed symptom ratings [3,4,25,28], it can be concluded that DSM-based rating scales are useful instruments for assessing disruptive behavior problems in children and adolescents across different contexts.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In addition, the study provides initial evidence for the factorial validity of teacher ratings of DSM-IV-TR-defined symptoms of ODD and CD in clinical populations. Since similar findings were reported for parent-completed symptom ratings [3,4,25,28], it can be concluded that DSM-based rating scales are useful instruments for assessing disruptive behavior problems in children and adolescents across different contexts.…”
Section: Discussionsupporting
confidence: 72%
“…Many of these are directly linked to the diagnostic criteria of the Diagnostic and Statistical Manual of Mental Disorders (DSM) [1] or the ICD-10 Classification of Mental and Behavioural Disorders [2] and ask the respondent to rate the presence and intensity of symptoms of oppositional defiant disorder (ODD) and conduct disorder (CD). Although parent-completed symptom rating scales are reliable and valid measures of disruptive behavior [3,4], several authors recommended to use additional information from teachers when making diagnostic decisions concerning ODD/CD [5]. …”
mentioning
confidence: 99%
“…The Children's Symptom Inventory (Sprafkin et al 2002) and the Aberrant Behavior Checklist (Aman et al 1985), were used for screening, based on guidelines used in prior treatment studies for children with PDDs (Research Units on Pediatric Psychopharmacology Autism Network 2002). Children scoring higher than 18 on the irritability scale of the ABC or scoring in the clinically significant range on any CSI scale were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…As an initial 2 Precedence for using shared variance to statistically derive central executive and/or storage/rehearsal variables is found in Kane et al (2004) and Swanson and Kim (2007). Sprafkin et al 2002). Previous studies also have shown that children with and without ADHD differ significantly on CBCL/TRF Social Problems items (e.g., Bagwell et al 2001).…”
Section: Social Problemsmentioning
confidence: 99%